2021
DOI: 10.1016/j.jhep.2021.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Low immunogenicity to SARS-CoV-2 vaccination among liver transplant recipients

Abstract: Background and aims Two SARS-CoV-2 mRNA vaccines were approved to prevent COVID-19 infection, with reported vaccine efficacy of 95%. Liver transplant (LT) recipients are at risk for lower vaccine immunogenicity and were not included in the registration trials. We assessed vaccine immunogenicity and safety in this special population. Methods LT recipients followed at the Tel-Aviv Sourasky Medical Center and healthy volunteers were tested for SARS-CoV-2 IgG antibodies dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
394
8
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(481 citation statements)
references
References 10 publications
47
394
8
7
Order By: Relevance
“…The second study from Tel-Aviv Sourasky Medical Center, Israel, evaluated humoral antibody responses in 80 LTR and 25 healthy volunteers after vaccination with the mRNA vaccine BNT162b2 (BioNTech/Pfizer). The study confirmed the concern of lower immunogenicity of vaccination in transplant recipients (reviewed in [1]); antibodies were detectable in only 47.5% of patients compared to all 25 healthy controls and antibody titers were significantly lower in LTR (95.41 AU/mL vs. 200.5 AU/mL, p<0.001) [3]. Importantly, the authors reported no serious adverse events associated with the vaccine, and no event of graft rejection was observed.…”
Section: Editorialsupporting
confidence: 71%
See 2 more Smart Citations
“…The second study from Tel-Aviv Sourasky Medical Center, Israel, evaluated humoral antibody responses in 80 LTR and 25 healthy volunteers after vaccination with the mRNA vaccine BNT162b2 (BioNTech/Pfizer). The study confirmed the concern of lower immunogenicity of vaccination in transplant recipients (reviewed in [1]); antibodies were detectable in only 47.5% of patients compared to all 25 healthy controls and antibody titers were significantly lower in LTR (95.41 AU/mL vs. 200.5 AU/mL, p<0.001) [3]. Importantly, the authors reported no serious adverse events associated with the vaccine, and no event of graft rejection was observed.…”
Section: Editorialsupporting
confidence: 71%
“…This lead the European Association for the Study of the Liver (EASL) to publish a position paper guiding COVID-19 vaccination in patients with CLD, hepatobiliary cancer, and liver transplant recipients (LTR) [1]. In this issue, Wang et al [2] and Rabinowich et al [3] report first data on COVID-19 vaccination in patients with nonalcoholic fatty liver disease (NAFLD) and liver transplant recipients.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…Deepak et al observed a threefold lower generation of anti-SARS-CoV-2 spike IgG and neutralizing antibodies in patients with chronic inflammatory diseases undergoing immunosuppressive treatment compared to immunocompetent controls [24]. Similar evidence was collected from other studies in patients receiving various immunosuppressive agents after transplantation [18,[25][26][27][28] or treatment for chronic inflammatory conditions [29], but also in patients with different forms of cancer [30], especially in those with hematological malignancies [31,32], as well as in subjects with end-stage renal disease [33].…”
Section: Why?mentioning
confidence: 52%
“…55,73 The formation of neutralizing antibodies in liver transplant recipients (especially those receiving immunosuppressants) have been suboptimal, as shown by a recent study. 74 The clinical impact of this suboptimal response remains to be seen. However, this should not deter any clinician from prescribing the vaccine in these patients.…”
Section: Vaccinationmentioning
confidence: 99%